PENSION PROVISION OF CITIZENS OF ODESA DURING THE OCCUPATION IN 1941–1944 (Південний архів (історичні науки), 2022)
Research’s purpose: This work analyses laws of Romanian occupational government, related to the pensions and the state of pension provisions of the Odessa citizens in 1941–1944. The results of this research must be helpful for better understanding of life, economical behaviour and survival strategies of the population of Transnistria during the Second world war. It would also provide a better picture of how social care and the laws which enforce it were implemented by occupational government. Research methods: The work is based on source studies methods, methods of archival heuristics, comparison of sources and statistical methods. Results and conclusions of the research: We analysed all normative and regulative documents related to the question of social payments to the population of Odessa and Transnistria in 1941–1944. We have also researched archive funds of the Governorate, the Pension Department and the Labor Department of the Odessa Municipality in The State Archives of Odessa Region. We have developed the methods to estimate the headcount of citizens, whose life was influenced by new law, and the headcount itself. We have evaluated the effectiveness of the orders of the Romanian occupational government related to the social care. We have discovered the institutions responsible for the distribution of social welfare in the occupied region. We studied of all newspaper titles, related to the subject, and discovered the ways of informing the locals about new laws. The work contains information about the amount and the ways of providing social payments, fund and sums spent to conduct those payments in 1943–1944. For the first time were discovered social groups that were provided with social care, and the ones that were rejected for pensions. In conclusion, after total exterminating of Jewish and Gypsy population, Romanian occupational administration took care about social payments for soviet citizens of the Transnistria region, who belonged to other social and ethnical groups. Even though the occupational regime was, by all means, unethical, it took ethical steps to stabilize its own ruling position in society and avoid possible rebellions on controlled territories.
Keywords: Second World War, Odessa, Transnistria, population, Romanian occupation